Lignocellulosic plant cell wall variation influences the structure and properties of hard carbon derived from sorghum biomass. (April 2022) - Afzal, Rana Arslan; Pennells, Jordan; Yamauchi, Yusuke; Annamalai, Pratheep K.; Nanjundan, Ashok Kumar; Martin, Darren J.
Highlights: Sorghum (Sugargraze™) biomass was partitioned into leaf, sheath, and stem sections. Biomass carbonisation yielded uniquely structured carbon from different sections. Carbon properties are related to biomass features e.g., lignocellulosic composition. Potential for tunable carbon features through controlled biomass selection. Abstract: Agricultural by-products offer attractive renewable feedstock options for the production of carbon to be used as electrode materials for energy storage applications. Developing insights into the carbonisation behaviour of these alternative feedstocks will enable us to tune the materials and processing conditions effectively. For the first time, this study reports the influence of lignocellulosic biomass variation on the structure and properties of sorghum-derived hard carbon materials. Four primary plant sections of sorghum biomass (leaf, sheath, upper stem and bottom stem), with different lignocellulosic composition and hierarchical native plant cell wall morphology, were partitioned from the harvested biomass and subsequently carbonised. Thermal and structural analysis of these sections before and after carbonisation revealed that both the morphology and associated lignocellulosic composition were influential upon the structure and properties of the resultant carbon. The leaf section with the highest lignin and ash content yielded 23% carbon, with high crystallinity and a higher existence of graphite-like domains. It also exhibited a highly porous structure and a large specific surface area. The sheath section with the highest cellulose content yielded 26% carbon with thinner graphitic layers and a larger d -spacing compared to other sections. Stem sections with high extractives facilitated early-stage stabilisation. The upper stem, which had the lowest lignin and ash content, yielded 25% carbon with the lowest BET surface area and pore volume. In contrast, the bottom stem yielded 30% carbon with more disordered turbostratic hard carbon and a lower d -spacing compared to other sections. It is noted that a higher graphitic carbon ratio can be achieved by selecting a biomass precursor with a higher lignin content and lower crystallinity index. Additionally, the value of BET surface area and pore volume strongly correlates with starting lignin content. This research contributes to developing a more sophisticated and comprehensive understanding of how the subtle structural and compositional variations present in different plant sections of sorghum biomass can influence the properties of carbonised materials, hopefully aiding the future potential for enhanced tunability of sustainable biomass-derived carbon products. Graphical abstract: Image, graphical abstract